Implementasi Algoritma Artificial Bee Colony dalam Penentuan Rute Terpendek Perusahaan Ekspedisi - Windayani, Ni Wayan; Pramartha, Cokorda Rai Adi (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2022)
Delivery service is a promised business so many new companies are opening this business. However, it is not uncommon for parcel delivery to be delayed. From the field of Informatics, determining the courier route is included in the Traveling Salesman Problem. The TSP problem can be solved using several algorithms, one of which is the Artificial Bee Colony or ABC algorithm. Artificial Bee Colony algorithm adapted from the behavior of bee colonies in search of food. In this study, primary data is used in the form of destination points in the Bangli sub-district area of ??PT Global Jet Express Bangli delivery of packages using 20 destination points. The results of this system showed that the three parameters tested, namely the number of bees, the maximum limit and the maximum iteration did not show significant changes for the best distance. In this study, the shortest distance obtained using the Artificial Bee Colony algorithm is the number of bees is 10, the limit is 20 and the maximum iteration is 40 with a value of 38,42 km.